1996
DOI: 10.1037/0033-2909.120.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse in individuals exposed to trauma: A critical review.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
431
1
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(474 citation statements)
references
References 269 publications
(402 reference statements)
30
431
1
12
Order By: Relevance
“…Such self medication behavior, however, is typically seen as an avoidance coping strategy, which is usually not associated with positive outcomes (23,24,54,56). Thus, it is entirely possible that attempts at alcohol withdrawal may actually intensify symptoms for individuals with PTSD or depression (15,18,55). These reactions may interfere with the resolution of the traumatic experience, prolonging symptoms following the disaster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such self medication behavior, however, is typically seen as an avoidance coping strategy, which is usually not associated with positive outcomes (23,24,54,56). Thus, it is entirely possible that attempts at alcohol withdrawal may actually intensify symptoms for individuals with PTSD or depression (15,18,55). These reactions may interfere with the resolution of the traumatic experience, prolonging symptoms following the disaster.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals my use substances like alcohol to cope with symptoms associated with psychological problems (54,55). For example, alcohol use may dampen the physiological responses related to PTSD such as hyperarousal or re-experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…Youth with CU traits also tend to be highly reward-sensitive , leading them to seek out substances regardless of their environmental context. The association between violence exposure and drug use or related legal issues is often explained by the self-medication hypothesis, stating that the emotional sequelae of a traumatic event leads to subsequent substance use as a method of relieving painful symptoms or memories (Brown & Wolfe, 1994;Khantzian, 1985;Stewart, 1996). This process may help explain drug abuse among those who are both directly exposed to aggression through physical abuse or neglect and those who witness severe violence in the family or community; thus, the association is strengthened among CU individuals, who may be already susceptible to drug problems, particularly for this detained sample of boys.…”
Section: Exposure To Violence Mediates the Link Between Cu Traits Andmentioning
confidence: 99%
“…PTSD symptoms (Brady, Back, & Coffey, 2004;Stewart, 1996). Other studies have found AUD may increase risk of development of PTSD or be associated with a more severe and chronic course of symptoms (Acierno et al, 1999;Conrod & Stewart, 2003;Cottler et al, 1992).…”
mentioning
confidence: 98%